Incidence and disability-adjusted life-years of infective endocarditis in China from 1990 to 2021: comparison with G20 based on the Global Burden of Disease Study 2021 - Yan Gu; Chong Liu; Hong Chenliang; Zhu Weimin; Peng Qianping (BMJ Open)
Objectives Infective endocarditis (IE) is a global public health challenge, and our understanding of its temporal evolution in China compared with the Group of Twenty (G20) countries remains limited. This study aims to analyse the disease burden of IE in China from 1990 to 2021, forecast trends for the next 15 years and compare the findings with those in G20 countries.Design Observational study.Setting The data of 20 countries and regions in G20 were obtained from the Global Burden of Disease (GBD) Study 2021.Participants Data were publicly available and individuals were not involved.Main outcome measures Using data from the GBD 2021, we collected incidence, disability-adjusted life-years (DALYs) and age-standardised rates for both China and G20 countries. Temporal trends were assessed using the estimated annual percentage change (EAPC) and a joinpoint regression analysis was conducted to pinpoint periods of significant change. Additionally, a decomposition analysis was performed to identify the factors driving changes. Finally, the Bayesian age-period-cohort model was used to forecast trends for the next 15 years.Results In 2021, there were 264 282 (95% UI: 216 083 to 315 405) incident cases of IE in China, resulting in 49 925 (95% UI: 38 779 to 69 119) DALYs. The age-standardised incidence rate (ASIR) and age-standardised DALY rate (ASDR) were 14.38 (95% UI: 12.03 to 16.92) and 3.46 (95% UI: 2.65 to 5.01) per 100 000 population, respectively, with both rates being higher in males than in females. Notably, both ASIR and ASDR showed a pattern of first decreasing and then increasing with age, with the highest values observed in the age group of 95 years and above. From 1990 to 2021, the ASIR of IE in China showed a slow upward trend (EAPC: 0.49, 95% CI: 0.44 to 0.55), which was lower than the average level among G20 countries. In contrast, the ASDR exhibited a significant downward trend (EAPC: −6.26, 95% CI: −6.8 to −5.71), representing the largest decline among the G20 countries. The most notable increase in ASIR occurred from 1995 to 2005 in both China and the G20. The greatest decrease in ASDR was observed in China between 2001 and 2004 and in the G20 between 2018 and 2021. Projections suggest that over the next 15 years, the ASIR for both males and females in China will continue to rise, while the ASDR will show a declining trend.Conclusions In China, the incidence of IE-related diseases has steadily increased across both genders, despite a declining trend in DALYs. Compared with G20 countries, China’s age-standardised burden of IE is relatively low, yet the large increasing number of cases should not be underestimated. Therefore, establishing effective prevention and treatment strategies is crucial to alleviating the future burden of IE.